Trafficking and release of Leishmania metacyclic HASPB on macrophage invasion - MacLean, Lorna; Seelenmeyer, Claudia; Nickel, Walter (Cellular microbiology, 2012)
Proteins of the Leishmania hydrophilic acylated surface protein B (HASPB) family are only expressed in infective parasites (both extra- and intracellular stages) and, together with the peripheral membrane protein SHERP (small hydrophilic endoplasmic reticulum-associated protein), are essential for parasite differentiation (metacyclogenesis) in the sand fly vector. HASPB is a ‘non-classically’ secreted protein, requiring N-terminal acylation for trafficking to and exposure on the plasma membrane. Here, we use live cell imaging methods to further explore this pathway to the membrane and flagellum. Unlike HASPB trafficking in transfected mammalian cells, we find no evidence for a phosphorylation-regulated recycling pathway in metacyclic parasites. Once at the plasma membrane, HASPB18-GFP (green fluorescent protein) can undergo bidirectional movement within the inner leaflet of the membrane and on the flagellum. Transfer of fluorescent protein between the flagellum and the plasma membrane is compromised, however, suggesting the presence of a diffusion barrier at the base of the Leishmania flagellum. Full-length HASPB is released from the metacyclic parasite surface on to macrophages during phagocytosis but while expression is maintained in intracellular amastigotes, HASPB cannot be detected on the external surface in these cells. Thus HASPB may be a dual function protein that is shed by the infective metacyclic but retained internally once Leishmania are taken up by macrophages.